Sonic Hedgehog Is a Determinant of γδ T-Cell Differentiation in the Thymus - Mengrelis, Konstantinos; Lau, Ching-In; Rowell, Jasmine; Solanki, Anisha; Norris, Sonia; Ross, Susan; Ono, Masahiro; Outram, Susan; Crompton, Tessa (Frontiers in Immunology, 2019)
Here we investigate the function of Hedgehog (Hh) signaling in thymic γδ T-cell maturation and subset differentiation. Analysis of Hh mutants showed that Hh signaling promotes γδ T-cell development in the thymus and influences γδ T-cell effector subset distribution. Hh-mediated transcription in thymic γδ cells increased γδ T-cell number, and promoted their maturation and increased the γδNKT subset, whereas inhibition of Hh-mediated transcription reduced the thymic γδ T-cell population and increased expression of many genes that are normally down-regulated during γδ T-cell maturation. These changes were also evident in spleen, where increased Hh signaling increased γδNKT cells, but reduced CD27-CD44+ and Vγ2+ populations. Systemic in vivo pharmacological Smoothened-inhibition reduced γδ T-cell and γδNKT cells in the thymus, and also reduced splenic γδ T-cell and γδNKT populations, indicating that Hh signaling also influences homeostasis of peripheral γδ T-cell populations. Taken together our data indicate that Sonic Hedgehog is an important determinant of γδ T-cell effector subset differentiation.